PENGARUH LATIHAN HEXAGONAL OBSTACLE TERHADAP PENINGKATAN DAYA LEDAK POWER OTOT TUNGKAI - Achmad Nuryadi (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Power is the power and speed of muscle contraction is dynamic and explosive and involvesthe expenditure of maximum muscle strength in the fastest time. Explosive power is one componentof physical condition that is needed in sports. This is supported by the opinion of Sukadiyanto(2011: 128) power is the result of times between strength and speed. To that end, the sequence toincrease power is given after the athlete is trained element of strength and speed. According toRiaydi, (2010) explosive power is a person's ability to use maximum capabilities deployed in theshortest time. The obstacle hexagonal jump is done quickly so that the movements performed areexplosive or abrupt so as to have an effect on the increase of explosive muscle limb power. Theresult of statistical analysis showed that the mean for the treatment group was 2.90 while the meanfor the control group was 1.55 this indicated that the mean group of threatment was greater than thecontrol group. While the results of the threatment group analysis is known that the t-test value is11.599 with the standard deviation of 1.119 and for the control group that the t-test value is 9.131with the standard deviation of 0.759, thus there is indeed the effect of obstacle hexagonal exerciseon increasing the muscle explosive power ) leg muscles.